Measuring underwater noise with high endurance surface and underwater autonomous vehicles - Silva, A. (2015)
This paper describes the results of AcousticRobot'13 - a noise measurement campaign that took place off the Portuguese Coast in May 2013, using two high endurance autonomous vehicles capable of silent operation (an underwater glider and an autonmomous sailing vessel) equipped with hydrophones, and a moored hydrophone that served as reference. We show that the autonomous vehicles used can provide useful measurements of underwater noise, and describe the main advantages and shortcomings that became evident during the campaign.